Emerging indigenous voices : safeguarding intangible heritage in Colombia and the reaffirmation of cultural rights (2012)
Indigenous cultural heritage protection in Colombia is supported by the human right to self-determination and the provisions of the Indigenous and Tribal Peoples Convention, 1989 (ILO 169). The recent ratification of the Intangible Cultural Heritage Convention, 2003 (CSICH) in 2008 has added to this legislative basis, most notably by highlighting that cultural heritage is not static, and its elements - while being protected - must be allowed to evolve in time. The Colombian legal approach is analyzed, first by discussing the shift from the historical focus on tangible hentage to the fluid nature of intangible heritage: and then by considering how this shift holistically acknowledges and protects cultural rights and multicultural identities. The listmg of the "'Traditional Knowledge of the Jaguar Shamans of Yurupari" is used as a case study ofthe appropriation of the CSICH and its implementation instruments by the Indigenous communities of the Great Vaupes Reservation in the Colombian eastern Amazon.